2015
DOI: 10.1523/jneurosci.4255-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of the Glutamate Transporter GLT-1 Reveals That Astrocytic GLT-1 Protects against Fatal Epilepsy While Neuronal GLT-1 Contributes Significantly to Glutamate Uptake into Synaptosomes

Abstract: GLT-1 (EAAT2; slc1a2) is the major glutamate transporter in the brain, and is predominantly expressed in astrocytes, but at lower levels also in excitatory terminals. We generated a conditional GLT-1 knock-out mouse to uncover cell-type-specific functional roles of GLT-1. Inactivation of the GLT-1 gene was achieved in either neurons or astrocytes by expression of synapsin-Cre or inducible human GFAPCreERT2. Elimination of GLT-1 from astrocytes resulted in loss of ϳ80% of GLT-1 protein and of glutamate uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
278
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 261 publications
(295 citation statements)
references
References 85 publications
15
278
2
Order By: Relevance
“…The mice appeared normal with normal lifespan. From this it was concluded that astroglial EAAT2 is the main protector against excitotoxicity (Petr et al, 2015) in agreement with the distribution of the EAAT2 protein.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
See 3 more Smart Citations
“…The mice appeared normal with normal lifespan. From this it was concluded that astroglial EAAT2 is the main protector against excitotoxicity (Petr et al, 2015) in agreement with the distribution of the EAAT2 protein.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
“…In agreement, it was shown electron microscopically that D-aspartate accumulates preferentially (85 %) in the terminals in synaptosome preparations (Furness et al, 2008). This was tested using conditional knockout mice: when EAAT2 was selectively deleted in neurons (using synapsin-Cre mice), then the uptake activity in synaptosome preparations was reduced to half (Petr et al, 2015; see also Fig. 4).…”
Section: Resealing Probability Favors Neuronal Eaat2 In Synaptosome Pmentioning
confidence: 62%
See 2 more Smart Citations
“…For immunoblot analysis, astrocytes or striatal tissue were lysed by frosting and defrosting in lysis buffer (containing Tris HCl 0.2 M, pH 8, and Protease Inhibitor 1ϫ, Sigma) and centrifuged at 10,000 ϫ g for 10 min at 4°C as described previously (Petr et al, 2015): mouse anti-␤-actin (1:15000; Santa Cruz Biotechnologies); mouse anti-EAAT2/GLT-1 (1: 1000; Millipore clone G6); and rabbit anti-EAAT1/GLAST (1:500; Abcam). Western blots were quantified measuring optical densities of immunoreactive protein bands (in vitro only monomer of GLT-1 was present) using ImageJ or Image Laboratory (Bio-Rad Laboratories) software, normalizing results to ␤-actin values.…”
Section: Methodsmentioning
confidence: 99%